A randomised, double masked, clinical trial of high dose vitamin A and vitamin E supplementation after photorefractive keratectomy - Vetrugno, M. (2001)
AIM—To evaluate the effect of a high dose vitamin A and E supplementation on corneal re-epithelialisation time, visual acuity and haze following photorefractive keratectomy (PRK). METHODS—Two groups of 20 patients who underwent myopic PRK were supplemented with either 25 000 IU retinol palmitate and 230 mg α( )tocopheryl nicotinate or a placebo. Clinical outcomes were evaluated up to 360( )days. RESULTS—In the vitamin treated group, re-epithelialisation time was significantly faster (p=0.029) and haze incidence was reduced (p=0.035), especially for high myopic corrections (p=0.043). This group also reported a significantly better uncorrected visual acuity (p=0.043). CONCLUSIONS—High dose vitamin A and E oral supplementation may accelerate re-epithelialisation time and may reduce corneal haze formation after PRK.